The Role of BKKBN Family Development Activity Group Cadres In Increasing Understanding Of Stunting In Palangka Raya City - Anwar Ginoto; Farid Yopiannor (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This study aims to understand the role of cadres in improving family awareness about stunting, as well as to explore cadres' perceptions regarding the incidence of Low Birth Weight (LBW) infants and the development of stunting cases in their areas of responsibility. The study uses a qualitative method with a case study approach, conducted in the Jekan Raya and Pahandut sub-districts of Palangka Raya City, from October to January 2025. Data collection techniques include observations and in-depth interviews with informants selected through purposive sampling, specifically cadres with deep knowledge about the research topic. The data collected will be analyzed using interactive qualitative analysis, which involves three main stages: data reduction, data presentation, and conclusion drawing. The study’s results are expected to provide a clear picture of the role of cadres in stunting prevention and support the development of targeted intervention programs to reduce stunting rates in these areas. The results show that the communities in Jekan Raya and Pahandut have a good understanding of stunting and its prevention. The majority of respondents know that stunting is caused by malnutrition and affects child development. They also understand the importance of the 1000 HPK period and preventive measures such as prenatal check-ups and exclusive breastfeeding. Although there are some misconceptions regarding the duration of the 1000 HPK period and the measurement of upper arm circumference in pregnant women, stunting prevention efforts in the region have been quite effective.